Historical trend of hourly extreme rainfall in Peninsular Malaysia - Abdul Halim, Syafrina; M.D., Zalina; Liew, Juneng (Springer, 2015)
Hourly rainfall data between the years 1975 and 2010 across the Peninsular Malaysia were analyzed for trends in hourly extreme rainfall events. The analyses were conducted on rainfall occurrences during the northeast monsoon (November--February) known as NEM, the southwest monsoon (May--August) known as SWM, and the two inter-monsoon seasons, i.e., March--April (MA) and September--October (SO). Several extreme rainfall indices were calculated at the station level. The extreme rainfall events in Peninsular Malaysia showed an increasing trend between the years 1975 and 2010. The trend analysis was conducted using linear regression; no serial correlation was detected from the Durbin-Watson test. Ordinary kriging was used to determine the spatial patterns of trends in seasonal extremes. The total amount of rainfall received during NEM is higher compared to rainfall received during inter-monsoon seasons. However, intense rainfall is observed during the inter-monsoon season with higher hourly total amount of rainfall. The eastern part of peninsular was most affected by stratiform rains, while convective rain contributes more precipitation to areas in the western part of the peninsular. From the distribution of spatial pattern of trend, the extreme frequency index (Freq >20) gives significant contribution to the positive extreme rainfall trend during the monsoon seasons. Meanwhile, both extreme frequency and extreme intensity (24-Hr Max, Freq >95th, Tot >95th, Tot >99th, and Hr Max) indices give significant contribution to the positive extreme rainfall trend during the inter-monsoon seasons. Most of the significant extreme indices showed the positive sign of trends. However, a negative trend of extreme rainfall was found in the northwest coast due to the existence of Titiwangsa Range. The extreme intensity, extreme frequency, and extreme cumulative indices showed increasing trends during the NEM and MA while extreme intensity and extreme frequency had similar trends during the SWM and SO throughout Peninsular Malaysia. Overall, the hourly extreme rainfall events in Peninsular Malaysia showed an increasing trend between the year 1975 and 2010 with notable increasing trends in short temporal rainfall during inter-monsoon season. The result also proves that convective rain during this period contributes higher intensity rains which can only be captured using short duration rainfall series.